Bilateral Chylothorax Complicating a Case of Chronic Lymphocytic Leukemia: A Case Report - Sharma, Munish (Clin Pract, 2017)
Chylothorax occurs when lymphatic fluid leaks from the thoracic duct and accumulates in the pleural space. Bilateral chylothorax caused by chronic lymphocytic leukemia (CLL) has been rarely reported in the literature. Sludging of lymph might be the underlying cause. We present a case of bilateral chylothorax in a patient with CLL.We also briefly discuss etiology, possible pathogenesis in our case along with diagnostic options and treatment modalities.